Partners for quality: building professional pathways for diverse adult learners in early childhood education - Karrie A. Snider (Emerald Publishing, 2024)
Purpose - This paper describes the rationale and key aspects of how one school-university partnership leveraged resources to create, implement and refine an innovative professional pathway called the Early Childhood Certificate (ECC) program which reflects the National Professional Development Schools (NAPDS) Essential Guideline 4: Reflection and Innovation. The ECC program is an innovative, career-building model that leverages resources between a predominantly white regional state university, a nonprofit organization serving as a Head Start grantee, a large urban school district and community-based education settings across a Midwestern metropolitan region. Design/methodology/approach - This descriptive narrative documents how the ECC program developed as a professional pathway for early childhood educators to scale up their skills for teaching young children while strengthening their capacities and credentials within the early childhood education (ECE) profession pipeline. The narrative includes relevant literature and examples from the field. Findings - This paper includes a discussion of the benefits and challenges related to the design, implementation and refinement of the professional learning ECC program. Research limitations/implications - This is a descriptive narrative. As such, generalizability is lacking. Research is needed to determine the effectiveness and sustainability of innovative teacher education programs. Practical implications - Relevant research and lessons learned provide guidance for other school-university partnerships to consider how to meet workforce and career needs for educators in the field of ECE. Social implications - School-university partnerships can be change agents and positively impact early childhood educators' career development. Originality/value - This paper addresses the need for understanding how predominantly white early childhood teacher education programs can partner with schools and agencies and then together leverage resources to support workforce and career development opportunities.